Implementation of a Philosophical Framework to Foster Critical Thinking in Islamic Education for Boarding School Students in Indonesia - Aziz, Adit Mohammad; Mokodenseho, Sabil; Komaruddin, Koko; Majdi, Ahmad Labib (Westscience Press, 2023)
Indonesian Islamic education, with its rich traditions, must change quickly to keep up with the times. This study investigates how philosophical frameworks are used in Indonesian Islamic boarding schools, or pesantren, and how they affect students' development of critical thinking abilities. A mixed-methods approach was used in the research, incorporating document analysis, observations, interviews, and surveys. With an average score of 3.78, the quantitative results showed a moderate level of philosophical framework integration within the program. With an average score of 4.21, students felt they had significantly improved their critical thinking abilities, indicating the usefulness of these frameworks. These outcomes were supported by qualitative data that emphasized students' excitement, teachers' acknowledgment of their ability, and administrators' support. Obstacles such limited resources, cultural awareness, and the requirement for teacher preparation were noted. Nonetheless, there are advantages to these difficulties as well, such as the chance to foster critical thinking and global competency. The study provides guidance for curriculum creators and policy makers, highlighting the possible advantages of incorporating philosophical frameworks into the larger educational environment.